Treatment retention and care transitions during and after the scale-up of HIV care and treatment in Northern Tanzania - Ostermann, Jan (2014)
Decentralization of HIV care is promoted to improve access to antiretroviral therapy in sub-Saharan Africa. This study describes care transitions among HIV-infected persons in Northern Tanzania during a period of rapid decentralization of HIV Care and Treatment Centers (CTCs) from hospitals to local health centers. Between November 2008 and June 2009, 492 HIV-infected patients in established care at two referral hospitals in Moshi, Tanzania, and 262 persons newly diagnosed with HIV were selected for participation in a prospective cohort study entitled Coping with HIV/AIDS in Tanzania. Clinical records and participant self-reports, collected between June and November 2012, were used to describe retention in care and transitions between CTCs during the study period. After a mean follow-up period of 3.5 years, 10 percent of participants had died, 9 percent were lost to follow-up, and 11 percent had moved. Of the remaining participants enrolled from CTCs, more than 90 percent reported at least one CTC visit during the previous six months, with 98 percent still in care at the CTC at which they were enrolled. Nearly 3 out of 4 newly diagnosed clients listed a referral hospital as their primary CTC. Fewer than 10 percent of participants ever sought care at another CTC in the study area; nearly 90 percent of those in care bypassed their closest CTC. Administrative data from all facilities in the study area indicate that new clients, even after the scale-up from 8 CTCs in 2006 to 21 CTCs in 2008, disproportionately selected established CTCs, and client volume at newly approved facilities was highly variable. Despite the decentralization of HIV care and treatment in this setting, many patients continue to bypass their closest CTC to seek care at established facilities. Patient preferences for HIV care, which may inform optimal resource utilization, are largely unknown and warrant further investigation.